Batch kinetics and effects of process parameters for biodegradation of Reactive Black 5 in an aerobic mixed microbial culture / Jagannathan Krishnan and Siti Rabiatul Adawiyah Ibrahim - Krishnan, Jagannathan; Ibrahim, Siti Rabiatul Adawiyah (Research Management Institute (RMI), 2013)
Mixed microbial culture used in this study was developed from sludge that was taken from local textile wastewater treatment tank. Acclimatization process was performed before starting the biodegradation experiment to obtain a microbial culture with high degradation properties. Kinetic studies by the mixed microbial culture were determined quantitatively for the model pollutant, Reactive Black 5 (RB 5). By using Michaelis-Menten model, the constants were found to be 11.15 mg 1-¹ h-¹ and 29.18 mg 1-¹ for Vm and Km respectively. The values of kinetic constants for Monod model were found to be 33.11 mg I-I cell h-¹ for the maximum specific microbial growth rate, µm and 86.62 mg 1-¹ for Monod constant, Ks ' The effects of process parameters such as pH, inoculum size and initial dye concentration on the biodegradation of azo dye, RB 5 were systematically investigated. Maximum removal efficiencies observed in this study were 75% for pH 6, 100% for 15% inoculum concentration and 750/0 for 20 ppm of initial dye concentration.